Kombuchas from green and black teas reduce oxidative stress, liver steatosis and inflammation, and improve glucose metabolism in Wistar rats fed a high-fat high-fructose diet. Issue 21 (7th October 2021) - Cardoso, Rodrigo Rezende; Moreira, Luiza de Paula Dias; de Campos Costa, Mirian Aparecida; Toledo, Renata Celi Lopes; Grancieri, Mariana; Nascimento, Talita Pimenta do; Ferreira, Mariana Simões Larraz; da Matta, Sérgio Luis Pinto; Eller, Monique Renon; Duarte Martino, Hercia Stampini; de Barros, Frederico Augusto Ribeiro
Abstract : Kombuchas from green and black teas are rich sources of phenolic compounds that reduced the metabolic changes induced by HFHF diet. Abstract : The aim of this study was to evaluate the effect of green and black tea kombuchas consumption on adiposity, lipid and glucose metabolism, liver steatosis, oxidative stress, and inflammation in Wistar rats fed a high-fat high-fructose (HFHF) diet. Wistar rats, after 8 weeks to induce metabolic alterations, were divided into an AIN-93M control group, HFHF control group, green tea kombucha + HFHF diet (GTK group), and black tea kombucha + HFHF diet (BTK group), for 10 weeks. The kombuchas improved glucose metabolism, plasma total antioxidant capacity, superoxide dismutase activity, and decreased nitric oxide concentration. Moreover, both kombuchas reduced systemic inflammation by decreasing the neutrophil/lymphocyte ratio (NLR), reduced the total adipose tissue and blood triglyceride, and reverted liver steatosis (from grade 2 to 1), besides the modulation of genes related to adipogenesis and β-oxidation. Therefore, kombuchas from green and black teas have bioactive properties that can help control metabolic alterations induced by the HFHF diet.